Exploring coping strategies of carers looking after people with intellectual disabilities and dementia - Perera, Bhathik D.; Standen, Penny (Emerald, 2014)
Purpose: Carers play a vital role in looking after people with intellectual disabilities (ID). Caring role can be stressful and challenging in nature. Carers use various coping strategies to deal with stressors. The purpose of this paper is to explore coping strategies of carers looking after people with ID and dementia.